Placental Malaria in Colombia: Histopathologic Findings in Plasmodium vivax and P. falciparum Infections (2013)
ABSTRACT: Studies on gestational malaria and placental malaria have been scarce in malaria-endemic areas of the Western Hemisphere. To describe the histopathology of placental malaria in Colombia, a longitudinal descriptive study was conducted. In this study, 179 placentas were studied by histologic analysis (112 with gestational malaria and 67 negative for malaria). Placental malaria was confirmed in 22.35%, 50.0% had previous infections, and 47.5% had acute infections. Typical malaria-associated changes were observed in 37%. The most common changes were villitis, intervillitis, deciduitis, increased fibrin deposition, increased syncytial knots, mononuclear (monocytes/macrophages and lymphocytes), polymorphonuclear cell infiltration, and trophozoites in fetal erythrocytes. No association was found between type of placental changes observed and histopathologic classification of placental malaria. The findings are consistent with those reported for placental malaria in other regions. Plasmodium vivax was the main parasite responsible for placental and gestational malaria, but its role in the pathogenesis of placental malaria was not conclusive.